PENGARUH PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN, DAN PERSEPSI KEAMANAN TERHADAP MINAT PENGGUNAAN E-MONEY (Studi Pada Pengguna Go-Pay di Kota Malang) - APRILLYA KARTIKA (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this research is to examine factors that affect the intent to use Go-Pay electronic money (e-money). The research was conducted in the City of Malang by using the survey method. This study uses a quantitative approach. The sampling technique used in this research is convenience sampling. The researcher obtained 180 respondents frompeople in Malang who had used Go-Pay e-money. The analysis was done using Smart Partial Least Square (PLS) software version 3.0. The results of the analysis for this model indicate that perceived usefulness, perceived ease of use, and perceived security positively affect the interest of using Go-Pay e-money. This means that the interest and intent to useGo-Pay e-money is influenced by perceived usefulness, perceived ease of use, and perceived security. The implications of this research are expected to provide input for the company to be used as consideration in improving service quality. Keywords: Perceived Usefulness, Perceived Ease of Use, Perceived Ease of Use, Perceived Security, Intent to Use Go-Pay E-Money